Mono‐Gold(I)‐Catalyzed Enantioselective Intermolecular Reaction of Ynones with Styrenes: Tandem Diels–Alder and Ene Sequence. Issue 2 (18th January 2021) - Nanko, Masaki; Inaba, Yuya; Sekine, Keisuke; Mikami, Koichi
Abstract: Gold‐catalyzed intermolecular reaction leading to dihydronaphthalene derivatives in one pot from two equivalents of ynones with respect to styrene is uncovered. The [4+2] Diels–Alder cycloaddition of ynones and styrenes is catalyzed by a mono‐gold(I) complex and the conjugated acid to provide an unstable 3, 8a‐dihydronaphthalene to subsequently undergo an intermolecular ene‐type reaction with the π‐activated ynone to afford multi‐component coupling dihydronaphthalene products. Linear relationships between chiral ligand‐gold complexes and chiral dihydronaphthalene products proves mono‐gold catalysis that triggers an asymmetric tandem Diels–Alder and ene reaction sequence. Abstract :